Wall pressure studies in a suddenly expanded flow for area ratio 2.56” - Baig, Maugal Ahmed Ali; Khan, Sher Afghan; Rathakrishnan, E. (IJERA, 2012)
This paper presents the results of an experimental work carried out to find the wall pressure distribution in a suddenly expanded duct. The enlarged duct is attached to the exit of a convergent- divergent axisymmetric nozzle. The area ratio (i.e. ratio between cross sectional area of the sudden expansion duct and the nozzle exit area) considered in the present study is 2.56. The jet entering the suddenly expanded duct is at supersonic Mach numbers regime of 1.87, 2.2 and 2.58. The length to diameter ratio considered is 10. The nozzle pressure ratio (NPR) used is 3, 5, 7, 9, and 11 for all the Mach numbers. An active control method in the form of Microjets is used to control the base pressure. The prime investigations are towards finding the effect of Microjets on wall pressure for above said parametric conditions. It is found that the duct wall pressure distribution, which usually becomes oscillatory when controls are employed, does not get adversely affected with Micro jets.